Estudio codisciplinar de la Matemática en la escuela secundaria: análisis de la gestión de una propuesta de aula para el estudio del crecimiento de plantas - Emanuel Berardi; Ana Rosa Corica (Ikastorratza.e-Revista de Didáctica, 2023)
This paper presents the results of the management of a didactic device formulated by a Mathematics male and Biology female teacher from a secondary school in which they sought a codisciplinary study. Based on the Anthropological Theory of the Didactic, the results of an exploratory study that sought to characterize the management of a didactic device for the study of plant growth in secondary school are reported; In particular, we analyze the relevance of mathematical knowledge in its development. The main results indicate that the study enabled the protagonists to be the students: they formulated and answered questions, achieving autonomy and responsibility for the search for information in various media; however, mathematical knowledge did not occupy a prominent place during the study.